PEMBERIAN ZAT PENGATUR TUMBUH (ZPT) ALAMI PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) DI MAIN-NURSERY - Sudarso '; Nelvia '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research aims to study the provision of plant growth regulator (PGR) from banana weevil and shoots on the growth of oil palm seeds (Elaeis guineensis Jacq) in the main-nursery. The experiment was conducted in a greenhouse of Faculty of Agriculture, University of Riau in October 2013 to January 2014. Testing in the form an experiment using Completely Randomize Design (CRD) that consists of 3 treatment (without PGR, PGR of the bananas weevil: 75 ml and PGR of the bamboo sprout : 75 ml), every treatment repeated 4 times. Parameter that observed are high quality seeds, the number of leaves and the diameter weevil. Results of the study showed that the original PGR of bamboo sprout and bananas weevil influential was real increase seeds, the number of foot and mouth diameter weevil that without PGR. The original PGR of bamboo sprout  increase each parameter higher than PGR of the bananas weevil.   Keyword: Oil  palm and Plant Growth Regulator